Organizational Relationships In The Self-Managed Enterprise - Adizes, Ichak (Universidad del Pacífico, 1974)
The article discusses the conditions under which the self-management model for enterprises would work with success. It resumes the flaws found in Yugoslavia to exemplify how these conditions could work if the right method is applied.